3D Printed Hybrid Electrodes for Lithium-Ion Batteries. (7th July 2017) - Li, Jie; Leu, Ming; Panat, Rahul; Park, Jonghyun
Abstract : A novel hybrid 3D structured electrode, with a high-aspect ratio, is fabricated via extrusion-based additive manufacturing to achieve high mass loading and combine the advantages offered by a conventional laminated structure and a 3D digital structure. This structure is designed to enhance interfacial reactions and species transport by utilizing the 3D structure. Two key challenges in 3D structured electrodes are addressed, including solution preparation and scale-up. The paste is optimized with a high viscosity to avoid the typical complexity encountered in preparing a solution for 3D printing, and the proposed hybrid 3D structures can be easily added to the conventional laminated structures. This is demonstrated by using a CR2032 coin cell, which also solves the typical assembly problems that occur with 3D structured electrodes. This innovative design and fabrication process demonstrates high areal energy and power density, which are critical requirements for energy storage systems in transportation and stationary applications.